Abundance of Perifiton as Natural Fish Food in The Banjaran River, Banyumas Indonesia - Al Hidayah; Rahayu, Nur Laila; Zaenuri, Musyarif (Universitas Atma Jaya Yogyakarta, 2025)
Fresh waters in Indonesia are strongly broad and play a role for aquaculture as well as human activities, thus impacting water quality and river ecosystems. Periphyton acts as a natural food source. This study aimed to determine the abundance of periphyton species as natural food for fish in the Banjaran River, and the quality of river water. Survey method and purposive sampling were used and conducted at four stations. This research was conducted in situ and ex situ and the test results were analyzed descriptively quantitatively. The percentage of periphyton abundance the Banjaran River is 28% from the class Bacillariophyceae (25 species), 21% Chlorophyceae (9 species), 21% Cyanophyceae (3 species), 16% Eugelenophyceae (2 species), and 16% Rhizopoda class (1 species). The abundance of periphyton at each station was 3,275–5,574 individuals/cm² with species abundance values of 26–22,904 individuals/cm², while the percentage values for the abundance of each class were Bacillariophycae (82%), Chlorophyceae (9%), Eugelenophyceae (6%), Cyanophyceae (2%), and Rhizopoda (1%). The water quality that greatly influences the value of periphyton abundance is TDS (Total Dissolved Solid). The influence of TDS content on the abundance of periphyton was 0.8 and the influence was negative.